Cosmetic Outcomes of Supraorbital Keyhole Craniotomy Via Eyebrow Incision: A Systematic Review and Meta-Analysis - Robinow, Zoe M.; Peterson, Catherine; Riestenberg, Robert; Waldau, Ben; Yu, Nina; Shahlaie, Kiarash (Journal of Neurological Surgery Part B: Skull Base, 2022)
Background Supraorbital eyebrow craniotomy is a minimally invasive alternative to a frontotemporal craniotomy and is often used for tumor and vascular pathologies. The purpose of this study was to investigate how patient cosmetic outcomes are affected by technique variations of this approach.Methods PubMed, Embase, and Scopus databases were systematically searched, and results were reported according to PRISMA guidelines. For the meta-analysis portion, the DerSimonian–Laird random effects model was used, and the primary end points were patient satisfaction and percentage of permanent cosmetic complications.Results A total of 2,629 manuscripts were identified. Of those, 124 studies (8,241 surgical cases) met the inclusion criteria. Overall, 93.04 ± 11.93% of patients reported favorable cosmetic outcome following supraorbital craniotomy, and mean number of cases with permanent cosmetic complications was 6.62 ± 12.53%. We found that vascular cases are associated with more favorable cosmetic outcomes than tumor cases (p = 0.0001). Addition of orbital osteotomy or use of a drain is associated with adverse cosmetic outcomes (p = 0.001 and p = 0.0001, respectively). The location of incision, size of craniotomy, utilization of an endoscope, method of cranial reconstruction, skin closure, use of antibiotics, and addition of pressure dressing did not significantly impact cosmetic outcomes (p > 0.05 for all).Conclusions Supraorbital craniotomy is a minimally invasive technique associated with generally high favorable cosmetic outcomes. While certain techniques used in supraorbital keyhole approach do not pose significant cosmetic risks, utilization of an orbital osteotomy and the addition of a drain correlate with unfavorable cosmetic outcomes.
Keywords: cosmesis; eyebrow; keyhole; orbital osteotomy; supraorbital; technique